The effect of acute caffeine ingestion on upper and lower body anaerobic exercise performance. Issue 10 (26th November 2019) - Duncan, Michael J.; Eyre, Emma; Grgic, Jozo; Tallis, Jason
Abstract: The current study examined the effect of acute caffeine ingestion on mean and peak power production, fatigue index and rating of perceived exertion (RPE) during upper body and lower body Wingate anaerobic test (WANT) performance. Using a double-blind design, 22 males undertook one upper body and one lower body WANT, 60 min following ingestion of caffeine (5 mg*kg −1 ) and one upper body and one lower body WANT following ingestion of placebo (5 mg*kg −1 Dextrose). Peak power was significantly higher ( P  = .001) following caffeine ingestion in both upper and lower body WANT. Peak power and mean power was also significantly higher during lower body, compared to upper body WANTs irrespective of substance ingested. However, caffeine ingestion did not enhance mean power neither in upper nor lower-body WANT. There were no significant differences in mean fatigue index as a consequence of substance ingested or mode of exercise (all P  > 0.05). For RPE there was also a significant substance ingested X mode interaction ( P  = .001) where there were no differences in RPE between caffeine and placebo conditions in lower body WANTs but significantly lower RPE during upper body WANT in the presence of caffeine compared to placebo ( P  = .014). This is the first study to compare the effects of caffeine ingestion on upper and lower body 30-second WANT performance and suggests that caffeine ingestion in the dose of 5 mg*kg −1 ingested 60 min prior to exercise significantly enhances peak power when data from upper and lower body WANTs are combined.